Synthetic aperture source localization. (19th December 2019) - Waddington, Chad; Cheney, Margaret; Given, James A
Abstract: Many state-of-the-art methods in source localization require large numbers of sensors and perform poorly or require additional sensors when emitters of interest transmit highly correlated waveforms. We present a new source localization technique which employs a cross correlation measure of the time difference of arrival (TDOA) for signals recorded at two separate platforms, at least one of which is in motion. This data is backprojected through a process of synthetic aperture source localization (SASL) to form an image of the locations of the emitters in a region of interest (ROI) This method has the advantage of not requiring any a priori knowledge of the number of emitters in the scene. Nor does it rest on an ability to identify regions of the data which come from individual emitters, though if this capability is present it may improve image quality. We demonstrate that this method is capable of localizing emitters which transmit highly correlated waveforms, though complications arise when several such emitters are present in the scene. We discuss these complications and strategies to mitigate them.